Geo-Congress 2022 : Geophysical and Earthquake Engineering and Soil Dynamics : selected papers from Geo-Congress 2022, March 20-23, 2022, Charlotte, North Carolina. - Lemnitzer, Anne; Stuedlein, Armin Wilhelm, 1978- (Geotechnical special publication ;, 2022)
GSP 334 contains 70 peer-reviewed papers on soil dynamics and earthquake engineering presented at Geo-Congress 2022, held in Charlotte, North Carolina, March 20-23, 2022.